Construction of a sustained-release hydrogel using gallic acid and lysozyme with antimicrobial properties for wound treatment. (2nd November 2022) - Gong, Wei; Huang, Hai-bo; Wang, Xin-chuang; He, Wan-ying; Hou, Yi-yang; Hu, Jiang-ning
Abstract : The purpose of this study is to provide a new strategy for constructing a temperature-controlled hydrogel as a promising agent for wound healing using natural products through physical co-assembly. Abstract : The purpose of this study is to provide a new strategy for constructing a temperature-controlled hydrogel as a promising agent for wound healing using natural products through physical co-assembly. Herein, the temperature-controlled physically assembled hydrogel consisting of gallic acid and lysozyme (GL) could be co-assembled into a regular fibrous structure accompanied by strong blue fluorescence with three-dimensional networks at micron levels through hydrophobic interactions, π–π interactions and hydrogen bonding. This GL hydrogel has excellent temperature sensitivity and self-healing properties, as proved by cycle high-low temperature tests. In addition, it possesses stable rheological properties, great sustained release ability, and could realize the spatiotemporal delivery of gallic acid and lysozyme. Biocompatibility and antibacterial tests proved that this well-assembled GL hydrogel has no cytotoxicity but excellent antibacterial activity. Both in vitro and in vivo experiments demonstrated that the GL hydrogel has excellent anti-inflammation efficiency and promotes the healing of chronic wounds by suppressing the expression of pro-inflammatory related genes. Tests using an E. coli -infected wound model confirmed that the GL hydrogel could terminate the inflammatory phase early and ultimately promote the healing of wounds infected by E. coli . This study provides a promising strategy for the effective treatment of wounds through a physical self-assembled hydrogel.